Relationship between Competency, Motivation and Workload of Implementing Nurses with Nurse Performance in the Inpatient Room at Bangkinang Hospital - Asmara Fitra Abadi; Suarni Norawati (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
The performance of nurses in the inpatient room at Bangkinang Hospital can be seen from the quality of nursing services provided, oriented to better patient outcomes. The performance of nurses is influenced by the characteristics of nurses, competence, motivation and workload. The purpose of this study was to determine the relationship between the competence, motivation and workload of implementing nurses with the performance of nurses in the inpatient room at Bangkinang Hospital. The study used a cross sectional analytic design. A sample of 111 nurses in the inpatient room was taken using a total sampling technique. Data were collected using questionnaires and observation sheets, then analyzed bivariate with chi-square test and multivariate with logistic regression test. The results showed that there was a significant relationship between competence, motivation and marital status with the performance of nurses, with p values ​​for each variable, namely aspects of competence (p < 0.001), aspects of motivation (p < 0.001). Meanwhile, marital status (AOR = 4.5) and this relationship were not statistically significant (p = 0.095). Nurse performance is closely related to the competence and work motivation of nurses, so aspects that can improve competence and work motivation need to be managed properly to get good nurse performance results.